No Null-Helix Mannheim Curves in the Minkowski Space E13 - Jae Won Lee (International Journal of Mathematics and Mathematical Sciences)
We study a null Mannheim curve with time-like or space-like Mannheim partner curve in the Minkowski 3-space E13. We get the characterization of a null Mannheim curve. Then, we investigate there is no null-helix Mannheim curve in E13.